Milton’s Paradise Lost: Previously Unrecognized Allusions to the Aurora Borealis, and a Solution to the Comet Conundrum in Book 2 - Cunningham, Clifford J. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
This article reveals that John Milton employed an allusion to the aurora borealis in book 6 (79–83) of Paradise Lost, unrecognized in more than three centuries of scholarly analysis. Two other likely allusions, and one certain, to the aurora have also been identified. This research casts doubt on the long-held belief, made popular by the astronomer Edmund Halley (1656–1742), that no notable aurora was visible in England in the seventeenth century. After examining an overlooked note by the English historian William Camden (1551–1623), this article explores the possibility that Milton actually saw an aurora. A solution is also presented here to the long-standing conundrum of the comet near the “Arctic” constellation Ophiuchus in book 2 (707–11) of Paradise Lost.